2017
DOI: 10.11138/mltj/2017.7.3.478
|View full text |Cite
|
Sign up to set email alerts
|

MRI evaluation to predict tendon size for knee ligament reconstruction

Abstract: SummaryBackground: The aim of this study is to evaluate a possible correlation between specific anthropometric parameters and sizes of knee tendons commonly used for ACL reconstruction. We hypothesized that specific clinical and radiological knee measurements could be better tendon sizes predictors than age, gender, height and weight. Materials and methods: 100 consecutive patients were enrolled and 77 patients met the inclusion criteria of the study. All patients underwent a MRI of the knee with a 1.5 T super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(17 reference statements)
0
17
0
1
Order By: Relevance
“…Also to obtain the full mechanical benefits of the graft, it is suggested that all proximal ligament attachment sites identified in this study might be considered during graft fixations, in addition to the posteroinferior aspect of the acetabular fossa that is commonly used as a fixation site (Simpson et al, 2011;Philippon et al, 2012;Mei-Dan and McConkey, 2014). Studies at the knee joint have demonstrated that an anatomical structure serving mechanical stability to a joint correlates to articular or body size (Camarda et al, 2018;Matsumoto et al, 2018). In the hip, it is also reported that the size of the FCF and the HOF correlate with each other and the femoral length (Hay, 1996;Perumal et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also to obtain the full mechanical benefits of the graft, it is suggested that all proximal ligament attachment sites identified in this study might be considered during graft fixations, in addition to the posteroinferior aspect of the acetabular fossa that is commonly used as a fixation site (Simpson et al, 2011;Philippon et al, 2012;Mei-Dan and McConkey, 2014). Studies at the knee joint have demonstrated that an anatomical structure serving mechanical stability to a joint correlates to articular or body size (Camarda et al, 2018;Matsumoto et al, 2018). In the hip, it is also reported that the size of the FCF and the HOF correlate with each other and the femoral length (Hay, 1996;Perumal et al, 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Studies at the knee joint have demonstrated that an anatomical structure serving mechanical stability to a joint correlates to articular or body size (Camarda et al, ; Matsumoto et al, ). In the hip, it is also reported that the size of the FCF and the HOF correlate with each other and the femoral length (Hay, ; Perumal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Table I. Following critical review of these papers the highest correlation score of 0.86 4 was achieved with only one surgeon and only one measurement at two times magnification. The 0.4 score seen in one paper 2 used a more robust technique of four times magnification and repeat measurements similar to our technique.…”
Section: Agreement Between Pre-operative Mr and Intraoperative Graftmentioning
confidence: 97%
“…Our aim was to determine the reproducibility of MR graft measurements between two readers pre-operatively and to produce a measure of accuracy, rather than correlation between the MR measurements and the actual graft size. The previous literature has attempted pre-operative measurements of hamstring diameter and cross sectional area [1][2][3][4][5][6] . The diameter readings have shown poorer correlation and therefore we have focused on cross sectional area of the tendons as per the existing literature.…”
Section: Mri Scans Do Not Accurately Predict Hamstring Graft Diametermentioning
confidence: 99%
See 1 more Smart Citation